Strategies from the 2000-01 Ebola outbreak in Uganda - F G Omaswa, FRCS; S I Okware, PhD; E Kiguli-Malwadde, MMed (Elsevier, 2015)
Background: An outbreak of Ebola virus disease was reported from Gulu district, Uganda, on Oct 8, 2000. Over a period of 3 months, the outbreak spread to two other parts of the country, namely Mbarara and Masindi districts. Response measures included surveillance, community mobilisation, and case and logistics management. Three coordination committees were formed: the National Task Force (NTF), the District Task Force (DTF), and the Interministerial Task Force (IMTF). The NTF and DTF were responsible for coordination and follow-up of implementation of activities at the national and district levels, respectively, while the IMTF provided political direction and handled sensitive issues related to stigma, trade, tourism, and international relations. This study documents this experience and draws lessons that are of interest to the rest of the world. Methods: The international response was coordinated by the WHO under the umbrella organisation of the Global Outbreak and Alert Response Network. A WHO and Centers for Disease Control and Prevention case definition for Ebola was adapted and used to capture four categories of cases: alert cases, suspected cases, probable cases, and confirmed cases. Guidelines for identification and management of cases were developed and disseminated to people responsible for surveillance, case management, contact tracing, and information, education, and communication. Findings: For the duration of the epidemic that lasted to Jan 16, 2001, 425 cases with 224 deaths were reported throughout Uganda. The case fatality rate was 53%. The attack rate (AR) was highest in women. The average AR for Gulu district was 12·6 cases per 10 000 inhabitants when the contacts of all cases were considered, and was 4·5 cases per 10 000 if limited only to contacts of laboratory confirmed cases. The secondary AR was 2·5% when nearly 5000 contacts were followed up for 21 days. Uganda was finally declared free of Ebola on Feb 27, 2001, 42 days after the last case was reported. The Government's role in coordination of both local and international support was of huge importance. The NTF and the corresponding district committees worked closely in the harmonised implementation of the mutually agreed programme. Community mobilisation using community-based health workers, cultural and religious leaders, and Members of Parliament was effective in transmitting information to the public. Interpretation: Past experience in epidemic management shows that, in the absence of free availability of information to the public, rumours that are unhelpful to epidemic control efforts prevail and spread quickly. During this outbreak in Uganda, rumour was managed by frank and open discussion of the epidemic, daily updates, fact sheets, and press releases. Information was regularly disseminated to communities through mass media and press conferences. Community mobilisation and transmission of information to the public was critical in controlling the epidemic. All levels of the community spontaneously demonstrated solidarity and response to public health interventions-even in areas of relative insecurity, where the number of rebel abductions dropped considerably during the outbreak. Funding: None.